La investigacion en campos de agricultores en el altiplano de Quetzaltenango, Guatemala - Castro L., O.R.; Bolaños, S.; Guerra, E.; Orozco, E (International Center for Tropical Agriculture, 1987)
The 5 activities carried out as part of the project of generation, evaluation, and validation of on-farm technology at the Quetzaltenango plateau in Guatemala are described. These activities include agricultural and socioeconomic studies, germplasm selection in exptl. stations, on-farm trials, sample plots, and evaluation of new technology and its acceptance by farmers. One of the most important aspects of technology transfer is the multiplying effect accomplished by the agricultural guides, hired and trained in the new technologies by the transfer promoters and extensionists. (CIAT)